1998
DOI: 10.1002/clc.4960210709
|View full text |Cite
|
Sign up to set email alerts
|

Telemetry outside critical care units: Patterns of utilization and influence on management decisions

Abstract: SummaryBrrc.kground: Guidelines for the use of telemetry in hospitalized patients have been proposed by the American College of Cardiology (ACC). However. there have been only a few studies which have investigated the usefulness of these guidelines in clinical practice.H\pof/iesis: This study assessed the role of telemetry in the decision making process outside the critical care units. M i d d s :The observational shidy, lasting 4 weeks. was conclucted in the telemetry unit ofa tertiary care teaching hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…Many of the ‘not useful’ perceptions were motivated by the absence of an arrhythmic finding or of a subsequent medical interventions. For instance when electrolyte disturbances were the indication for the telemetry, electrolyte disturbances would have been treated in any case; when telemetry was prescribed for unclear symptoms, ECG monitoring was inconclusive in assessing the cause of symptoms (intermittent nature, transient duration, low prevalence of arrhythmias potentially responsible for symptoms), as in previous experiences []. In any case, the relevant but not clearly demonstrable role in reassuring physicians and patients, and in offering availability of a potential intervention should be taken into account.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Many of the ‘not useful’ perceptions were motivated by the absence of an arrhythmic finding or of a subsequent medical interventions. For instance when electrolyte disturbances were the indication for the telemetry, electrolyte disturbances would have been treated in any case; when telemetry was prescribed for unclear symptoms, ECG monitoring was inconclusive in assessing the cause of symptoms (intermittent nature, transient duration, low prevalence of arrhythmias potentially responsible for symptoms), as in previous experiences []. In any case, the relevant but not clearly demonstrable role in reassuring physicians and patients, and in offering availability of a potential intervention should be taken into account.…”
Section: Discussionsupporting
confidence: 78%
“…That telemetry monitoring was effective in HF patient’s management in non‐intensive care units, should be more than simply assumed. To our knowledge, only few studies have been previously published on the efficacy of ECG monitoring in guiding the decisional making of patients admitted to the non‐intensive unit []. Among them, the study of Estrada et al [] on more than 2000 patients, 277 with HF, concluded about an overestimate of the role of ECG monitoring because significant arrhythmias which modified the therapeutic strategy or induced an urgent treatment occurred only in a small subset of patients.…”
Section: Introductionmentioning
confidence: 99%
“…32 Nevertheless, continuous ECG monitoring (ie, telemetry) is expensive, labor-intensive and, potentially overutilized. 33,34 Requiring clinicians to place all patients receiving intravenous haloperidol on telemetry is impractical and potentially costly. Mandating telemetry could also lead to unintended harm, ie, use of a less effective or less safe drug to avoid compliance with the telemetry mandate.…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, Sivaram et al estimated the cost per patient at $683; in 2010, Ivonye et al published the cost difference between a telemetry bed and a nonmonitored bed in their inner-city public teaching facility reached $800. 3,4 In 1991, the American College of Cardiology published guidelines for telemetry use, which were later revised by the American Heart Association in 2004. 5,6 Notably, the guidelines are based on expert opinion and on research data in electrocardiography.…”
Section: Discussionmentioning
confidence: 99%